Ответы и объяснения

  • Участник Знаний
2013-06-21T12:27:42+04:00

f(x)=(x-8)(2x^2+x+4)

f'(x)=(x-8)'(2x^2+x+4) + (x-8)(2x^2+x+4)' = (2x^2+x+4) + (x-8)(4x+1) = 2x^2+x+4 + 4x^2+x - 32x-8 =

6x^2 -30x -4

Лучший Ответ!
  • AlbuRin
  • светило науки
2013-06-21T12:35:51+04:00

!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!

 

       f ' (x)   =  ((x-8)*(2x^2  +x   +4)  =  (x  -  8)' * (2x^2  +  x  +  4)   +   (x  -  8) *  (2x^2  +x  +  4)'=

 

   =    1  *  (2x^2  +  x  +  4)  +  (x  -  8) * (2 * 2x  +  1)  = 

 

  =     2x^2   +  x   +   4   +   4x^2  +  x    -    32x    -   8=

 

 

  =     6x^2   -   30x  -  4

 

Ответ.    6x^2    -   30x   -   4